The Role of Tax Incentives in Innovation Policies: theoretical considerations and recent developments - Gama e Colombo, Daniel (Revista Economia Ensaios, 2022)
The objective of this paper is to discuss the role of tax incentives as part of national innovation policies from a theoretical perspective. Tax incentives are commonly interpreted as closer to a market failure rationale, but they can also play a role as part of a broad evolutionary policy strategy. The theoretical debate provides a conceptual framework to explain the increasing relevance of tax incentives in different countries as from the 2008 economic crisis. The Brazilian experience seems inconsistent with this trend, as the reduction of public budget to innovation was not followed by an upsurge of tax incentives.